2011
DOI: 10.2139/ssrn.1753661
|View full text |Cite
|
Sign up to set email alerts
|

Long-Run Money Demand in OECD Countries – Cross-Member Cointegration

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…As a result, empirical estimations of money demand functions using panel data are widely captured in the literature (Bahmani 2015, Carrera 2008, Dreger and Wolters 2010, Dreger and Wolters 2014, Dobnik 2011, Elbadawi and Schmidt-Hebbel 2007, Fidrmuc 2009, Hamori 2008, Hamori and Hamori 2008, Harb 2004, Khalid et al 2010, Kjosevski et al 2016, Kumar et al 2013, Mark and Sul 2003, Nautz and Rondorf 2011, Tang 2007, Valadkhani 2008, Valadkhani and Alauddin 2003. Dilan and Örsal (2017) demonstrated that the long-run demand for money in 13 Organisation for Economic Co-operation and Development (OECD) economies was driven by the interdependence between cross-sections in the sample.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, empirical estimations of money demand functions using panel data are widely captured in the literature (Bahmani 2015, Carrera 2008, Dreger and Wolters 2010, Dreger and Wolters 2014, Dobnik 2011, Elbadawi and Schmidt-Hebbel 2007, Fidrmuc 2009, Hamori 2008, Hamori and Hamori 2008, Harb 2004, Khalid et al 2010, Kjosevski et al 2016, Kumar et al 2013, Mark and Sul 2003, Nautz and Rondorf 2011, Tang 2007, Valadkhani 2008, Valadkhani and Alauddin 2003. Dilan and Örsal (2017) demonstrated that the long-run demand for money in 13 Organisation for Economic Co-operation and Development (OECD) economies was driven by the interdependence between cross-sections in the sample.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Understanding the relationships between the money demand function and its determinants is important for exploring theories of macroeconomic behavior and implementing appropriate macroeconomic policies (Goldfeld 1994). Consequently, the demand for money and its functional specification has remained a contemporary issue subject to extensive empirical scrutiny in panel studies (Dobnik 2011, Dreger et al 2000, Garcia-Hiernaux and Cerno 2006, Lee and Chang 2013.…”
Section: Introductionmentioning
confidence: 99%
“…First, M1 is a good measure of liquidity in the economy, since it consists mainly of financial assets held for transaction purposes. Second, the central bank is able to control this aggregate more accurately than broader aggregates, such as M2 and M3 (Dobnik 2011). Third, M1 definitions tend to be relatively consistent across countries and therefore allow straight comparisons (Bruggeman 2000).…”
Section: Model Specification and Datamentioning
confidence: 99%
“…This variable is expressed by annual increase in CPI (annual percentage base 2005 = 100). We follow Valadkhani (2008), Ozturk and Acaravci (2008) and Dobnik (2011), who although including inflation in real M1, also included this variable as an independent determinant.…”
Section: Model Specification and Datamentioning
confidence: 99%
“…Some authors also use the exchange rate in the money demand specification to capture the effects from the substitution between domestic and foreign money (Dobnik 2011). However, we excluded the exchange rate from the money demand specification given the fact that the denar-euro exchange rate remained fixed for the analyzed period.…”
Section: Variable Selection and Data Transformationsmentioning
confidence: 99%